Psychological distress of residents in Kawauchi village, Fukushima Prefecture after the accident at Fukushima Daiichi Nuclear Power Station: the Fukushima Health Management Survey - Koji Yoshida; Tetsuko Shinkawa; Hideko Urata; Kanami Nakashima; Makiko Orita; Kiyotaka Yasui; Atsushi Kumagai; Akira Ohtsuru; Hirooki Yabe; Masaharu Maeda; Naomi Hayashida; Takashi Kudo; et al. (PeerJ, 2016)
Background To shed light on the mental health of evacuees after the accident at Fukushima Daiichi Nuclear Power Station (FDNPS), we evaluate the results of the Fukushima Health Management Survey (FHMS) of the residents at Kawauchi village in Fukushima, which is located less than 30 km from the FDNPS. Methods We conducted the cross-sectional study within the framework of the FHMS. Exposure values were “anorexia,” “subjective feelings about health,” “feelings about sleep satisfaction,” and “bereavement caused by the disaster,” confounding variables were “age” and “sex,” and outcome variables were “K6 points.” We collected data from the FHMS, and employed the Kessler Psychological Distress Scale (K6) and the posttraumatic stress disorder (PTSD) Checklist Stressor-Specific Version (PCL-S) to carry out the research. A total of 13 or greater was the cut-off for identifying serious mental illness using the K6 scale. The study subjects included residents (n = 542) of over 30 years of age from Kawauchi village, and data were used from the period of January 1, 2012 to October 31, 2012. Results A total of 474 residents (87.5%) scored less than 13 points in the K6 and 68 (12.6%) scored 13 points or more. The proportion of elderly residents (over 65 years old) among people with K6 score above the cut-off was higher than that among people with K6 score below the cut-off (44.1 vs 31.0%, p < 0.05). In addition, the proportion of residents with anorexia and mental illness among people with K6 score above the cut-off was higher than among people with K6 score below the cut-off (p < 0.001 and p < 0.05, respectively). The amount of residents who scored 44 points or more in the PCL-S among people with K6 score above the cut-off was also considerably higher than among people with K6 score below the cut-off (79.4 vs 12.9%, p < 0.001). Interestingly, the proportion of residents who scored more than among people with K6 score above the cut-off and the among people with PCL-S score above the cut-off in Kawauchi was higher than in previous studies in other locations. Conclusions These results suggest that there are severe mental health problems, such as depression and PTSD, among adults as a consequence of the accident at the FDNPS. Our study showed that residents who lived in the evacuation zone before the disaster are at high risk psychological distress. To facilitate local residents’ recovery from Fukushima, there is a need to continue providing them with physical and mental support, as well as communication regarding the health risks of radiation.